2021
DOI: 10.4236/jep.2021.125020
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Quality of a Forage Grass (<i>Pennisetum purpureum Schumach</i>) Used in Constructed Wetland Removing Domestic Wastewater Pathogenic Microorganism

Abstract: Constructed Wetlands (CWs) are an adequate wastewater treatment system with possibility to generate income, in particular by the use of plants of economic interest. However, very few studies deal with the bacteriological quality of plants after wastewater treatment. Thermotolerant coliforms and Sulfite-reducing bacteria were investigated on the above-ground biomass of a species of forage plant (Pennisetum purpureum) as well as their removal in an experimental pilot consisting of four beds, for three months. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Plants are known to release from their roots compounds that are readily utilized by microorganisms as carbon and energy sources. Zahui et al, (2021) reported the bacterial population in the rhizosphere of P. purpureum to reach 7.7×10 6 cfu/g in a constructed wetland and attributed it to exudates secreted by plants in the root zone. There are indication that high number of PAH degraders also correlates well with the amount of PAH biodegradation activity in soil and soils with a high total PAH content contain more PAH utilizers (10 5 -10 10 bacteria per gram of soil) than soils with low PAH content (Cerniglia, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Plants are known to release from their roots compounds that are readily utilized by microorganisms as carbon and energy sources. Zahui et al, (2021) reported the bacterial population in the rhizosphere of P. purpureum to reach 7.7×10 6 cfu/g in a constructed wetland and attributed it to exudates secreted by plants in the root zone. There are indication that high number of PAH degraders also correlates well with the amount of PAH biodegradation activity in soil and soils with a high total PAH content contain more PAH utilizers (10 5 -10 10 bacteria per gram of soil) than soils with low PAH content (Cerniglia, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the plants were equally well adapted to the shale-filled and laterite-filled constructed wetlands, as evidenced by the heights achieved (77.6 and 50.9 cm in the shale- and laterite-lined beds respectively) and the above-ground biomass produced (14.7 kg m −2 in the shale lite and 12.5 kg m −2 in the laterite lite). This is linked to the used nature of the water supplied to the different beds during experimentation, as indicated by Zahui et al [ 7 ]. However, P. purpureum grown in the natural environment produced larger stems and above-ground biomass compared with plants in constructed wetlands.…”
Section: Discussionmentioning
confidence: 99%
“…The beds were planted with P. purpureum seedlings (20 cm tall) from nurseries set up for this purpose on the experimental site. Three (3) plant seedlings of equal vigour were transplanted onto each bed, with a spacing of 30 cm between seedlings, relatively similar to that used by Zahui et al [ 7 ]. The beds were fed for three days during the week ( i.e.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations